2009 6th IEEE International Working Conference on Mining Software Repositories 2009
DOI: 10.1109/msr.2009.5069481
|View full text |Cite
|
Sign up to set email alerts
|

Does calling structure information improve the accuracy of fault prediction?

Abstract: Previous studies have shown that software code attributes, such as lines of source code, and history information, such as the number of code changes and the number of faults in prior releases of software, are useful for predicting where faults will occur. In this study of an industrial software system, we investigate the effectiveness of adding information about calling structure to fault prediction models. The addition of calling structure information to a model based solely on non-calling structure code attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Numerical, post-release fault prediction studies of other software products not related to Eclipse include (Bibi et al 2006;Kastro and Bener 2008;Khoshgoftaar and Munson 1990;Li et al 2006;Nagappan et al 2006;Ostrand et al 2004Ostrand et al , 2005Ostrand et al , 2010Bell et al 2006;Weyuker et al 2008;Shin et al 2009). Bibi et al (2006) compared twelve different models to determine the benefits of regression via classification.…”
Section: Numerical Prediction Of Post-release Software Faultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical, post-release fault prediction studies of other software products not related to Eclipse include (Bibi et al 2006;Kastro and Bener 2008;Khoshgoftaar and Munson 1990;Li et al 2006;Nagappan et al 2006;Ostrand et al 2004Ostrand et al , 2005Ostrand et al , 2010Bell et al 2006;Weyuker et al 2008;Shin et al 2009). Bibi et al (2006) compared twelve different models to determine the benefits of regression via classification.…”
Section: Numerical Prediction Of Post-release Software Faultsmentioning
confidence: 99%
“…The results showed that the individual developer's past performance was not an effective predictor of future bug locations. Shin et al (2009) used different combinations of LOC, static code metrics, change metrics, faults from previous releases, and calling structure information to construct negative binomial regression models. It appeared that the addition of calling structure information to a model based solely on non-calling structure code attributes provided noticeable improvement in prediction accuracy, but only marginally improved the best model based on history (i.e., change) and non-calling structure code attributes.…”
Section: Numerical Prediction Of Post-release Software Faultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schröter et al [17] showed that dependencies attributed to import statements in Java programs can be used to predict defects. Shin et al [18] and Naggappan and Ball [19] also used dependency information for defect prediction. Dependency relationships have been used by Zimmermann et al [20] to assess the quality of neighbouring entities.…”
Section: Introductionmentioning
confidence: 99%
“…D' Ambros et al (2009), Shin et al (2009), Nagappan et al (2010, and Madeyski and Jureczko (2015)). D 'Ambros et al (2009) specifically report that previous bug reports are the best predictors.…”
Section: Introductionmentioning
confidence: 99%